Development of phenol-formaldehyde resin with low formaldehyde emissions that respects LEED certification - Nadia Paiva (2014)
In the last years, production of particleboards with good overall performance and very low formaldehyde emission has been a challenge to wood based panels (WBP) industry, mainly since the re-classification of formaldehyde by the IARC (International Agency for Research on Cancer) as 'carcinogenic to humans (Group 1)'. Moreover, a new important limitation to the use of formaldehyde-based resins has been recently imposed by the LEED (Leadership in Energy and Environmental Design) certification for 'Green Building' construction: 'wood composites must contain no added urea-formaldehyde resins'. In this context, the main purpose of this study is to develop a PF resin for particleboard production that fulfils formaldehyde emission restrictions and LEED criteria, while presenting appropriate reactivity and bond strength. The mechanical performance and formaldehyde emissions of particleboards were optimized, changing both the resin synthesis and board production procedures. The synthesis process of these resins was carried out under an alkaline environment, and with an excess of formaldehyde towards phenol, in order to produce resol-type PF resins. The effect of changing the amount of added sodium hydroxide was studied. The particleboard production parameters were also changed, both in terms of blending conditions (amount of hardener and resin) and hot-pressing conditions (pressing time). A PF resin with very good internal bond strength, low formaldehyde strength and reasonable board pressing times was obtained using the following conditions: sodium hydroxide amount of 9% during the synthesis process, and 10% hardener (based on oven-dry weight of resin) together with gluing factor between 4.5 and 5% on the core layer during particleboard production. The best performing resin obtained demonstrated to be appropriate for use in the so called 'Green Building' construction.